Transition to Adulthood for Pediatric Moyamoya Patients - Scott, R Michael; Smith, Edward R. (Journal of Pediatric Neurology, 2020)
Moyamoya is a progressive arteriopathy of the intracranial vasculature, predominantly affecting the terminal branches of the internal carotid artery. Treatment is predicated on surgical revascularization to reduce the risk of stroke. For patients diagnosed and treated as children, it is important to recognize the long-term implications of the disease, for example, that moyamoya is treatable, but not curable. Pediatric moyamoya patients face unique challenges as they transition to adulthood as a consequence of the chronic nature of this disorder. Successful long-term care requires a strategy that incorporates ongoing longitudinal disease monitoring, coordination of care between physician teams, and anticipation of socioeconomic factors that change over time. This article provides an approach to transition care to adult caregivers for pediatric moyamoya patients with a specific focus on the three key stakeholders in the process: the neurosurgeon, the primary care physician, and the individual patient.
Keywords: moyamoya; pediatric; adult; transition; cerebrovascular; stroke